Non-linear effects of industrial structure on urban haze pollution: A test and extension of the environmental Kuznets curve - Wang, Zhenhua; Dai, Ruijie; Yang, Jian; Bai, Bing; Jiang, TianLong (Frontiers in Environmental Science, 2022)
Whether the Environmental Kuznets curve is established in haze pollution has an important policy. Based on the PM2.5 concentration raster data of 283 cities in MODIS and MISR, this paper empirically examines the non-linear effects of industrial structure upgrading on haze pollution using a spatial econometric model, and further tests and extends the environmental Kuznets curve using a threshold model. The study finds that there is a significant spatial spillover effect on haze pollution between cities, an inverted ''U'' shaped relationship between industrial upgrading and haze pollution, confirming the environmental Kuznets curve, and that the effect of industrial upgrading on haze pollution is mainly a direct effect, while the indirect effect is not significant. Further discussion in this paper reveals that there is a threshold effect of industrial upgrading on haze pollution; the traditional environmental Kuznets curve can be refined and extended: on both sides of the inflection point, there may be both positive and negative effects of economic development on environmental pollution, and the environmental Kuznets curve is the result of the combined effect of the two different effects.